Understanding and Supporting Neurodiverse Software Developers in Agile Teams - Gama, Kiev; Lacerda, Aline (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2023)
The software development industry is gradually fostering diversity within its workforce. Recognizing that diverse teams often produce superior results, companies are increasingly committing to creating more inclusive environments. Diversity encompasses many dimensions such as gender, race/ethnicity, age, nationality, and neurodiversity. While gender has been the most extensively addressed dimension in software engineering research, the focus on neurodiversity has been primarily directed towards users, rather than developers. Developers with Autism Spectrum Disorder (ASD) and Attention Deficit Hyperactivity Disorder (ADHD) face unique challenges due to difficulties with executive functions, the cognitive processes essential for behavioral control. These processes include skills such as inhibitory control, cognitive flexibility, working memory, and planning, all of which are vital for effective teamwork and job performance. In this pilot study, we attempt to fill the existing knowledge gap about neurodiverse software developers. Using a socio-technical grounded theory approach, we investigate the challenges these developers face and explore how adjustments to agile team practices could enhance their comfort. The emergent results from this study present promising insights and implications for research about neurodiverse software developers, contributing to a more inclusive and productive workplace environment.